Asal Usul Penamaan Hari Perspektif Mitologi - Nur Afdal Purnama Putra; Izzuddin, Ahmad (UIN ALAUDDIN MAKASSAR, 2024)
“A calendar is a marking instrument that makes it easier for someone to mark days and seasons. In the calendar cycle used today, it is agreed that there are 7 days in a week, namely Monday to Sunday, which then raises the question of where the name of these days came from and why they are called that. To answer this, a qualitative research study will be carried out which is library research. This article tries to answer why there are seven days in a week and where the names of the days come from from a mythological perspective so that we will find answers to the history of the origins of the naming of days from a mythological perspective because ancient nations were very steeped in their myths.”